2006
DOI: 10.1164/rccm.200512-1861oc
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of Lung Function Changes with Humoral Immunity during Inhaled Human Insulin Therapy

Abstract: The small lung function changes observed with INH therapy are not mediated by the humoral immune response, or associated with acute decrements in lung function immediately after insulin inhalation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 27 publications
4
37
0
Order By: Relevance
“…Consistent with previously published short-term data (11)(12)(13)(14), the present study demonstrates that EXU therapy is equally as effective in maintaining glycemic control as SC insulin while generally having a similar safety profile and minimal impact on lung function.…”
Section: ])supporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previously published short-term data (11)(12)(13)(14), the present study demonstrates that EXU therapy is equally as effective in maintaining glycemic control as SC insulin while generally having a similar safety profile and minimal impact on lung function.…”
Section: ])supporting
confidence: 91%
“…By using nonstandardized lung function testing, trials of EXU in adult type 1 diabetic patients identified small treatment group differences in lung function over 6 months, favoring SC insulin (12,13). A subsequent short-term (3-month) study in type 1 diabetic patients using standardized methodology showed that these differences occurred early and were not progressive after 2-4 weeks, were clinically insignificant, and resolved within 2 weeks of discontinuation of treatment (14).…”
mentioning
confidence: 99%
“…[13][14][15][16][17][18] The magnitude of reduction in FEV1 was similar in both type 1 and type 2 diabetes patients.…”
Section: Forced Expiratory Volume In 1 Secondmentioning
confidence: 80%
“…Moreover, differences in FEV1 between the treatment groups resolved within two weeks of discontinuation of inhaled insulin. 15 Similarly, in a 24-week cross-over study, small reductions in baseline FEV1 were observed within two weeks of initiating inhaled insulin therapy and were reversible upon discontinuation of therapy. 18 The results of a longer-duration study of inhaled insulin in type 1 diabetes patients indicate that the initial reductions in FEV1 occurred within the first three months of therapy and were significantly different between treatment groups following one year of therapy (mean annual rates of decline in FEV1…”
Section: Forced Expiratory Volume In 1 Secondmentioning
confidence: 95%
See 1 more Smart Citation